Is Enough Being Done to Train Teachers in Special Educational Needs in Ireland? - McGuire, Sally (Trinity College (Dublin, Ireland). School of Education, 2022)
Inclusive Education is prevalent in both Irish and International literature and policy when talking about students with Special Educational Needs. In order for Ireland to fully adopt an Inclusive Education System and provide a meaningful education for all learners, the barriers to inclusive education must be examined and broken down. This study looks solely at the barrier of the training teachers receive in inclusive practices, and investigate if enough is being done to train teachers in Special Educational Needs in Ireland. This study used a qualitative approach to collect the opinions of in-service teachers in a DEIS, rural Secondary School in County Wexford Ireland. The study consisted of 25 teachers who all completed an online surveys, and 3 of the participants took part in structured, one to one interviews, to give their opinion on the training they received in Special Educational Needs. The research in this study showed that teachers feel under prepared and lacked confidence in their ability to include students with Special Educational Needs fully in their classes. This stems from not receiving adequate levels of training in Special Educational Needs when in their initial teacher training and also the lack of availability of on-going training while they are in-service. This study finished with recommendations on the next steps to providing teachers with the training they feel they need, along with the building of a unifying Special Educational Needs module, which would allow all teachers to be at the same place in their knowledge of Special Educational Needs when they enter the classroom.
Keywords: Special Educational Needs; Education